THE EFFECTIVENESS OF THE TECHNOLOGY OF PREPARATION OF FUTURE TEACHERS FOR CONTINUOUS PROFESSIONAL SELF-DEVELOPMENT - Фрицюк, В. А. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
Technology of prospective teachers’ training to uninterrupted professional self-development meets generally accepted methodological requirements, which are put forward to the so-called technological criteria: conceptuality, systematization, handling, effectiveness and reproducibility. Conceptuality is provided by scientific conception which contains a philosophical, psychological, socio-pedagogical justification for achieving the planned purpose. Systematization of the developed technology presupposes existence of all system features: logic of the process, the interconnection of individual parts, integrity. Handling provides the possibility of diagnostic aim-establishing, planning, design of learning process, staged diagnostics, variation of means and methods for the purpose of results correction. Effectiveness of this technology indicates that it should have effective results and be optimal for the expenses and it ensures the achievement of a certain standard. Reproducibility provides the possibility of applying this technology in other similar educational institutions and by other individuals